1998
DOI: 10.1038/nm0398-298
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the contact-phase system on bacterial surfaces—a clue to serious complications in infectious diseases

Abstract: Fever, hypotension and bleeding disorders are common symptoms of sepsis and septic shock. The activation of the contact-phase system is thought to contribute to the development of these severe disease states by triggering proinflammatory and procoagulatory cascades; however, the underlying molecular mechanisms are obscure. Here we report that the components of the contact-phase system are assembled on the surface of Escherichia coli and Salmonella through their specific interactions with fibrous bacterial surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 26 publications
7
156
0
Order By: Relevance
“…In addition to its role in hemostasis, the blood clotting system plays an important role in host defense against pathogens by stimulating inflammation, fibrin deposition, and possibly other mechanisms (19)(20)(21)(22). In addition, the contact pathway of blood clotting, although dispensable for normal hemostasis, appears to play important roles in kinin generation and host-pathogen interactions (23).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its role in hemostasis, the blood clotting system plays an important role in host defense against pathogens by stimulating inflammation, fibrin deposition, and possibly other mechanisms (19)(20)(21)(22). In addition, the contact pathway of blood clotting, although dispensable for normal hemostasis, appears to play important roles in kinin generation and host-pathogen interactions (23).…”
Section: Resultsmentioning
confidence: 99%
“…Binding assays were performed as previously described (15). Briefly, 200 l of bacterial suspensions were incubated with 25 l (ϳ8 ϫ 10 5 cpm/ml) radioactively labeled protein for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…When injected into animals, curli-expressing bacteria disrupt the coagulation cascade by modulating the contact system and trigger inflammatory reactions by activating inducible nitricoxide synthase (12,15,16). Moreover, it has been observed that E. coli bacteria expressing curli and a mutant strain secreting soluble CsgA stimulate a human macrophage cell line to produce proinflammatory cytokines (17).…”
mentioning
confidence: 99%
“…Agf fibers are fimbrial organelles that bind Congo red and soluble fibronectin (14), contact phase proteins (31), and promote adhesion to the mouse small intestinal epithelial cells (23). As the mutation responsible for the altered agf expression was unknown, we used a transposon mapping approach to identify the locus responsible.…”
Section: Mapping a Locus Associated With Agfa Fimbrial Expression Andmentioning
confidence: 99%